Diagnostic performance of CT and MRI in Diagnosis of Diseases involving Pterygopalatine Fossa - Mingkwansook, Varalee; Chabnak , Lalita; Dechasasawat, Thanapat; Watcharakorn, Arvemas (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: To evaluate the diagnostic performance of CT and MRI in diagnosis of pterygopalatine fossa lesions and to describe disease entities involving pterygopalatine fossa (PPF). Methods: The CT and MRI images of 29 patients who had the PPF lesions were retrospective reviewed by two neuroradiologists who were blinded to the diagnosis. The radiologist’s interpretation was one of four categories; benign soft tissue tumor, malignant soft tissue tumor, primary bone tumor, and inflammatory lesion. The results were compared to final diagnosis and calculated for sensitivity, specificity, accuracy, PPV, NPV, and interobserver agreement. Results: Of the 29 cases, 18 were malignant soft tissue tumor (62%), 2 were benign soft tissue tumor (7%), 3 were primary bone tumor (10%), and 6 were inflammatory lesion (21%). Benign soft tissue tumor demonstrated highest specificity, accuracy, PPV and NPV (100%). Both benign and malignant soft tissue tumor equaled in highest sensitivity (100%). The interobserver agreement showed substantial agreement (Kappa = 0.744, P-value < .001). Conclusions: CT and MRI have high accuracy in diagnosis of the pterygopalatine fossa lesions with high sensitivity in the detection of benign and malignant soft tissue tumor. However, there was low specificity in diagnosis of the malignant soft tissue tumor because of overlapped findings in malignant tumors and aggressive inflammation.